Does this fit my style? The role of self-congruity in young women's repurchase intention for intimate apparel. Issue 4 (3rd October 2016) - Vigolo, Vania; Ugolini, Marta Maria
Abstract : Purpose: The purpose of this paper is to investigate the role of actual and ideal congruity in predicting the repurchase intentions of young women in relation to inconspicuous fashion items. Design/methodology/approach: The research focussed on a non-luxury intimate apparel brand, typical of daily use and private consumption. Regression analyses were conducted on a sample of 308 young female consumers to identify the effect of actual and ideal congruity in determining repurchase intentions. A cluster analysis based on actual self-concept was employed to develop a typology for consumers. Findings: Unexpectedly, the findings revealed that ideal congruity is a stronger predictor of repurchase intentions than actual congruity. Further, based on actual self-concept, three profiles of young women emerged: active romantics, self-assureds and reliables. The clusters differed in relation to perceptions of brand personality and the effect of self-congruity on repurchase intentions. Research limitations/implications: This study was conducted using participants from one university in Northern Italy. Thus, the main limitations of this study relate to sample size and selection. Additionally, this study only investigated the perceptions of young women. Practical implications: This study suggests that non-luxury intimate apparel items, typical of daily use, are not merely functional purchases, but reflect young women's self-expression motives. Accordingly, fashion marketers should focus on consumers' ideal self-concepts to develop effective promotion strategies. Further, specific dimensions of brand personality should be considered in relation to the different clusters. Originality/value: This study shows that repurchase intentions towards inconspicuous non-luxury fashion items are explained more by self-esteem motives (i.e. ideal congruity) than self-consistency motives (i.e. actual congruity).